Downregulation of Light-Harvesting Complex II Induces ROS-Mediated Defense Against Turnip Mosaic Virus Infection in Nicotiana benthamiana - Qiu, Shiyou; Chen, Xuwei; Zhai, Yushan; Cui, Weijun; Ai, Xuhong; Rao, Shaofei; Chen, Jianping; Yan, Fei (Frontiers in Microbiology, 2021)
The light-harvesting chlorophyll a/b complex protein 3 (LHCB3) of photosystem Ⅱ plays important roles in distribution of the excitation energy, modulating the rate of state transition and stomatal response to abscisic acid. However, the functions of LHCB3 in plant immunity have not been well investigated. Here, we show that the expression of LHCB3 in Nicotiana benthamiana (NbLHCB3) was reduced by turnip mosaic virus (TuMV) infection. When NbLHCB3 was silenced by tobacco rattle virus-induced gene silencing, systemic infection of TuMV was inhibited. H2O2 accumulated in NbLHCB3-silenced plants. Chemical treatment to inhibit or eliminate ROS impaired the resistance of NbLHCB3-silenced plants to TuMV infection. Co-silencing of NbLHCB3 with the ROS production genes AO or RBOHA compromised the resistance of plants to TuMV but co-silencing of NbLHCB3 with the ROS scavenging pathway genes increased resistance to TuMV. Transgenic plants overexpressing NbLHCB3 were more susceptible to TuMV. The results indicate that downregulation of NbLHCB3 is involved in defense against TuMV by inducing ROS production.